Algae Extraction Controllable Delamination of Vanadium Carbide Nanosheets with Enhanced Near‐Infrared Photothermal Performance. Issue 16 (28th February 2020) - Zada, Shah; Dai, Wenhao; Kai, Zhang; Lu, Huiting; Meng, Xiangdan; Zhang, Yiyi; Cheng, Yaru; Yan, Fang; Fu, Pengcheng; Zhang, Xueji; Dong, Haifeng
Abstract: The two‐dimensional (2D) vanadium carbide (V2 C) MXene has shown great potential as a photothermal agent (PTA) for photothermal therapy (PTT). However, the use of V2 C in PTT is limited by the harsh synthesis condition and low photothermal conversion efficiency (PTCE). Herein, we report a completely different green delamination method using algae extraction to intercalate and delaminate V2 AlC to produce mass V2 C nanosheets (NSs) with a high yield (90 %). The resulting V2 C NSs demonstrated good structural integrity and remarkably high absorption in near infrared (NIR) region with a PTCE as high as 48 %. Systemic in vitro and in vivo studies demonstrate that the V2 C NSs can serve as efficient PTA for photoacoustic (PA) and magnetic resonance imaging (MRI)‐guided PTT of cancer. This work provides a cost‐effective, environment‐friendly, and high‐yielding disassembly approach of MAX, opening a new avenue to develop MXenes with desirable properties for a myriad of applications. Abstract : V2 C nanosheets (NSs) were synthesized by a green method that is using algae extraction to etch bulk V2 AlC crystals in aqueous solution. The resulting V2 C NSs demonstrated good structural integrity and remarkably high absorption in near‐infrared (NIR) region with a high photothermal conversion efficiency (PTCE). The V2 C NSs can serve as an efficient photothermal agent for highly effective in vitro and in vivo photothermal ablation of tumors.